Exploring websites as a medium for constructing Moro awareness a descriptive study of selected Moro websites - Musor, Gonaranao B. (2005)
This study explored the potential of four Moro websites, namely www.bangsamoro.info, www.maranao.com, www.moroinfo.com, and www.luwaran.com, as tools for promoting Moro awareness. The overaching research methodology was reception analysis, specifically using web feature analysis and focus interviews of selected wensite visitors and webmasters of the said websites. Stuart Hall's Cultural Studies, Denis McQuail's Information Society theory, and Stanley Fish's Reader-Response theory comprised the study's framework. The four websites were found to promte Moro awareness in various ways:www.bandsamoro info. highlighted Moro and Mindanao history; www.maranao.com followed a magazine format featuring various news articles, essays, and literary works reflecting different facets of Maranao culture and way of life; and www.moroinfo.com and www.luwaran.com both focused on MILF-related issues and topics. Three of the websites were found to be still dependent on mainstream news articles, essays, and literary works reflecting different facets of Maranao culture and way of life; and www.moroinfo.com and www.luwaran.com both focused on MILF-related issues and topics. Three of the websites were found to be still dependent on mainstream news sources, which somehow turn them into mere online extension of these mainstream media outfits. Although the websites were seen to be effective in increasing the selected non-Muslims' knowledge about the Moros of Mindanao, this dies not necessarily the selected non-Muslim's knowledge about the Moros of Mindanao, this does not necessarily translate to a change in general perception of Moros, which is still mostly negative. The informants were mostly divided in considering whether or not the Internet is a viable and effective communication tool among Moros. Despite the advantages of the Internet seen by the informants, there is a need to address the problem of access identified as "technology gap" or "Digital Divide" still faced by most Filipinos, especially the Moros. The researcher, nevertheless, found that there is still plenty of hope that the problems of access, content, and participation in the various Moro websites by both Muslims and non-Muslims alike can indeed be overcome.
Vita.
Thesis (M.A. Communication)--University of the Philippines Diliman.
Keywords: Muslims -- Computer network resources. -- Philippines; Websites -- Philippines; Internet -- Social aspects